Barbara and John Chapman Visit Fresno - Watkins, Howard::::::::: (1979)
Dillon Williamson, Marcia McLane, Laurie Leifer, Ernestine Leas, Victor McLane, 2nd Sarah Williamson, Dee Shilling, Barbara Chapman, Julie Linxwiler, Daryl Balch, Dr. Lee Shilling; 3rd Adam Watkins, Christine Watkins, Jennifer Williamson, Hugh Williamson, Steve Kabot, John Chapman, Gregory Leifer, William Leifer, Florence Kabot.